Cardiovascular disease risk factors among older people: data from the National Health and Morbidity Survey 2015 - Shariff Ghazali, Sazlina; Sooryanarayana, Rajini; Ho, Bee Kiau; Omar, Mohd Azahadi; Krishnapillai, Ambigga Devi; Mohd Tohit, Noorlaili; Zainal Abidin, Sheleaswani Inche; Ariaratnam, Suthahar; Ahmad, Noor Ani (Public Library of Science, 2020)
Study on cardiovascular disease (CVD) risk factors and their prevalence among the older people in Malaysia is limited. We aimed to determine the prevalence and factors associated with CVD risk factors using the non-laboratory Framingham Generalized 10-Year CVD risk score among older people in Malaysia. This was a population-based cross-sectional study using data of 3,375 participants aged ≥60 years from the National Health and Morbidity Survey 2015. Sociodemographic, health factors and clinical assessments (anthropometry and blood pressure) were included. Complex survey analysis was used to obtain prevalence with 95% confidence intervals (CI). We applied ordinal regression to determine the factors associated with CVD risk. The prevalence for the high 10-year CVD risk was 72.1%. Body mass index was higher among those aged 60–69 years in men (25.4kg/m2, 95%CI 25.1–25.8) and women (26.7kg/m2, 95%CI 26.3–27.1) than the other age groups. The factors associated with moderate and high 10-year CVD risk were Malay ethnicity (Odds Ratio(OR) 0.76, 95%CI 0.63–0.92, p = 0.004), unmarried status (OR 1.55, 95%CI 1.22–1.97, p<0.001) and physically inactive (OR 0.72, 95%CI 0.55–0.95, p = 0.020). There is a need for future study to evaluate preventive strategies to improve the health of older people in order to promote healthy ageing.